FDEM Simulation on the Failure Behavior of Historic Masonry Heritages Subjected to Differential Settlement - Weibing Ou; Xudong Chen; Andrew Chan; Yingyao Cheng; Hongfan Wang (Buildings, 2022)
Historic masonry heritages, such as cathedrals, colonnades, and arch bridges, were constructed with individual components (e.g., stones, bricks, other materials) bound together with, e.g., mortar, and they are very vulnerable to foundation settlement, especially differential settlement which occurs frequently in engineering practice. These masonry structures are discontinuous, and therefore, their behavior under differential settlement is highly nonlinear and complex. In this study, the combined finite-discrete element method (FDEM) is employed to simulate the failure behavior of historic masonry heritages subjected to support differential settlement. In the FDEM models, structures are discretized into elements where FE formulation is incorporated, resulting in an accurate estimate of structural deformation and interaction forces. In addition, a fracture model is employed for masonry blocks. Numerical examples are given and compared with results from the literature, showing that the FDEM is applicable and reliable in simulating the failure behavior of historic masonry heritages. Further analyses including block fracture reveal that fracturing can decrease the capacity against settlement significantly.